Landscape and well-being: A conceptual framework and an example. (March 2019) - Yuill, Chris; Mueller-Hirth, Natascha; Song Tung, Nguyen; Thi Kim Dung, Nguyen; Tram, Pham Thi; Mabon, Leslie
This article explores why landscape is a crucial element in researching the relationship between environment and well-being. The main point we make is that human social agents are embedded in particular landscapes, and it is in landscapes that environmental changes are experienced, which can have implications for well-being. We draw from a variety of perspectives on landscape that understands a fundamental creative relation between humans and landscape and recent developments in neo-materialism theorising. Landscape is understood here as an assemblage of different forms of matter, animate and inanimate objects, as well as symbolic and cultural processes. A case study is also presented to indicate how landscape can be studied in relation to environment and change. Using the conceptual ideas laid out in the first section of the article, we analyse landscape, environment and well-being in Xuan Thuy National Park in North Vietnam. The area is part of a precarious coastal region where extreme weather events have impacted on the well-being of both humans and other matter. This article concludes with suggestions on the use of this landscape approach in researching environment and well-being.